2020
DOI: 10.18203/2349-2902.isj20204112
|View full text |Cite
|
Sign up to set email alerts
|

Influence of combined mechanical-chemical versus mechanical bowel preparation on anastomotic leak and surgical site infections after elective resection of left colon cancer

Abstract: Background: Mechanical bowel preparation (MBP) before elective resection of left colon cancer remains controversial. We propose that the protective effect of MBP is dependent on its combination with chemical preparation by oral antibiotics.Methods: Medical data of adult patients with left colon cancer who underwent elective resection at Sohag University Hospital (August 2016-March 2019) were reviewed. Anastomotic leak (AL), surgical site infections (SSI), postoperative morbidity and mortality were compared amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…To simplify the ranking process, complication score in each patient was concluded via assigning one points to each complication level in ascending order. 16 We found that cirrhotic patients who had major resections (all in the huge HCC group) developed more serious complications and required longer periods of hospital stay. These findings were in agreement with previous studies which showed increased postoperative complications following huge HCC ≥10 cm resection in cirrhotics compared with those with smaller HCCs.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…To simplify the ranking process, complication score in each patient was concluded via assigning one points to each complication level in ascending order. 16 We found that cirrhotic patients who had major resections (all in the huge HCC group) developed more serious complications and required longer periods of hospital stay. These findings were in agreement with previous studies which showed increased postoperative complications following huge HCC ≥10 cm resection in cirrhotics compared with those with smaller HCCs.…”
Section: Discussionmentioning
confidence: 80%
“…As we previously described, severity of postoperative complications was assessed by Clavien-Dindo system, with conclusion of postoperative complication score (ranging from one to seven) by assigning one point to each of the seven complication grades I, II, IIIa, IIIb, IVa, IVb and V in ascending order. 15,16…”
Section: Assessment Of Postoperative Complication Scorementioning
confidence: 99%
“…26,30 The severity of postoperative complications was objectively assessed by Clavien-Dindo system and our proposed scoring of grades of surgical complications. 21 In contrast to the non-elderly group, elderly patients, particularly cirrhotics, exhibited significantly higher complication score. This might be reasonably attributed to the poorer quality of liver parenchyma due to aging.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, severity of postoperative complications was assessed by Clavien-Dindo system. 21 Moreover, as we have previously described, each patient was given a postoperative score of complications (from one to seven) through assigning one point the seven grades which have been described in this system (I, II, IIIa, IIIb, IVa, IVb and V) in ascending order. 21 Mortality during the initial postoperative 30 days following liver resection, was considered as hepatectomy-related postoperative death, even if occurred after discharge from the hospital.…”
Section: Postoperative Assessmentmentioning
confidence: 99%